Neuro-Linguistic Programming Implementation Challenges in EFL Speaking Instruction: An Ethnographic Inquiry - Nurlaila Wattiheluw; Murni Mahmud; Amirullah Abduh (Universitas Sulawesi Barat, 2026)
Neuro-Linguistic Programming (NLP) is a structured pedagogical approach that integrates cognitive, affective, linguistic, and experiential dimensions in EFL speaking instruction. Although NLP has been considered theoretically promising, the practical challenges of its implementation in Indonesian higher education remain underexplored. Addressing this gap, the present study investigates the challenges encountered by an EFL lecturer during NLP implementation in speaking instruction. Employing a qualitative ethnographic design, data were collected over one full academic semester at UIN Saizu Purwokerto, Central Java, Indonesia, through in-depth interviews, participatory classroom observation, weekly student self-reflection, and documentary evidence. One experienced NLP-practising lecturer and twenty-five purposively selected students participated in the study. Data were analysed through ethnographic procedures involving inductive coding, contextual interpretation, and multi-source triangulation. Findings reveal five interconnected challenge dimensions: instructional design complexity, conceptual comprehension barriers, time constraints, linguistic challenges during speaking practice, and reflective evaluation difficulties. These findings collectively reconceptualise NLP as instructionally demanding and contextually grounded framework rather than a universally applicable method, contributing a rare ethnographic perspective to NLP research in Indonesian EFL higher education. Future research should examine institutional support strategies, including structured lecturer training, curriculum flexibility, and assessment reform, as well as conduct comparative studies across lecturers at varying NLP competency levels to determine whether the identified challenges are inherent to NLP as a pedagogical system or contingent on practitioner expertise.